Extremely happy holidays for exuberant grown-ups : wildly creative new cocktails to uplift and enchant through a full year of holiday chaos - McEwan, Devin C. B. (Running Press, an imprint of Hachette Book Group, Inc., 2025)
"What better way to honor and enjoy all the holidays of a year than to toast each one with a fabulous new cocktail? This exuberant little book takes you from New Year's Day all the way to New Year's Eve, with stops along the way at the other festive holidays of the year: Groundhog Day, Super Bowl Sunday, Valentine's Day, St. Patrick's Day, April Fools' Day, Easter, Cinco de Mayo, Mother's Day, Father's day, Independence Day, Talk Like a Pirate Day, Halloween, Thanksgiving, Hanukkah, and Christmas. McEwan's original creations are truly wonderful, and he is a droll ... guide through the tools and techniques the reader will need to make all these ... cocktails and mocktails at home"--